Efeitos cognitivos atencionais por meio de jogos recreativos em alunos do ensino fundamental - Santos, Rafaela Natale dos (2009)
Studies on cognitive functions and physical activity have increased the researches due to daily academic requirements. The physical exercises performed during the recreational games are seen as allies of children of the elementary level for a better cognitive performance, whereas the development of physical activity promotes the physiological, psychological and social conditions as a facilitator of more positive school learning. The attention is one of the most complexes and important of the cognitive functions for the development, that is characterized by the ability to filter out internal and external stimuli. The drawing is another important cognitive function in school performance; it can be used in the measurement of conceptual maturity of the child. Another ally to the cognitive stimulation are the games and fun activities, they are pleasurable and necessary for the social and moral development of the children, through them it is facilitated the acquisition of cooperative and competitive values. The purpose of this study is to identify the cognitive attention levels, pre and post program of recreational physical activity. The sample with the contribution of 37 participants: 18 boys and 19 girls with a 10-year-old-and-5-month average, attending the 4th grade of the elementary school in a public school. We evaluated the cognitive and attention levels, using the instruments: TEDIF-1 and TDFH. The comparative results of pre and post attention test showed gains after the intervention and statistically significant. The study demonstrated a superior performance of the boys in the qualitative-quantitative analysis, but in the girls, there were extreme scores on classification tracks, ie 47% higher zones (MS and ZS) and 21% in lower zones (ZI and MI), however, overall, the performance of the girls was below of the boys. This finding suggested a migration of performance, previously classified in ZI, MI and ZM to the most senior and MS and ZS, after the recreational activities, possibly by understanding and learning the task, resulting in an improved attention function. This was corroborated by the Wilcoxon Test in verifying pre-and post-test. In TDFH, the boys also had higher rates compared to the girls in the two test situations, but to compare the two drawings it was found that the girls had higher percentage rates than the boys in the category of improvement after intervention. It was observed that the participant, in drawing the figure of the same gender as their own, had higher scores, suggesting the influence of the sexual identification. The results showed the group of participants in the study had, cognitive and statistically, the performances attention function improved after the intervention, suggesting the effectiveness of the adopted recreation procedures.